2022
DOI: 10.3168/jds.2022-21935
|View full text |Cite
|
Sign up to set email alerts
|

An examination of labor time-use on spring-calving dairy farms in Ireland

Abstract: The seasonal workload associated with pasture-based dairy farms, combined with increasing herd sizes, has led to a renewed focus on labor time-use and efficiency on dairy farms. The objective of this study was to examine labor time-use on pasture-based dairy farms in the spring and summer seasons. A total of 82 spring-calving Irish dairy farms completed the study from February 1 to June 30, 2019 (150 d). Each farmer recorded their labor input on one alternating day each week using a smartphone app. Any labor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…In general, labor-saving ideas for the cow care task have not been identified by previous literature, despite it consuming 11% of total labor input during calving and breeding periods (Hogan et al, 2021). One technology that has been identified for its time-saving potential is automated heat detection (Adenuga et al, 2020), and this was one of the 12 work practices and technologies highlighted in this study for cow care.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In general, labor-saving ideas for the cow care task have not been identified by previous literature, despite it consuming 11% of total labor input during calving and breeding periods (Hogan et al, 2021). One technology that has been identified for its time-saving potential is automated heat detection (Adenuga et al, 2020), and this was one of the 12 work practices and technologies highlighted in this study for cow care.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence-based research is a key consideration for farmers when deciding to adopt new work practices and technologies (Borchers and Bewley, 2015), and there is a lack of evidence to-date of the time-saving potential of different labor-efficient work practices and technolo-gies. Using detailed information regarding labor input, and work practice and technology implementation on 76 dairy farms, this study identified 12 key laborefficient work practices and technologies (Tables 5 to 8) across the 4 most time-consuming farm tasks from February to June (Hogan et al, 2021), and estimated their potential labor-savings during the peak periods of workload for spring-calving dairy farms. Improved labor efficiency can enhance many key aspects of dairy farming including: reducing work hours (Deming et al, 2018), and improving health and safety for farm operators (Osborne et al, 2010); creating more attractive workplaces (Eastwood et al, 2020) and increasing farm profitability as influenced by labor costs (Hemme et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spring calving dairy herds are managed to synchronize the highest demand for feed (peak lactation) with the highest availability of grazed grass ( 33 ). This production system allows for farms to maintain higher levels of profitability due to the lower production costs of grass ( 34 ). It is recommended that 90% of the milking herd be calved within the first 6 weeks of the calving season ( 35 ).…”
Section: Introductionmentioning
confidence: 99%